TINJAUAN KESELAMATAN DAN KESEHATAN KERJA FAKTOR FISIKA TERHADAP PETUGAS REKAM MEDIS BAGIAN PENYIMPANAN BERKAS DI RUMAH SAKIT UMUM DAERAH CIBABAT CIMAHI - -, Suharto; Cahyani, Salwa Alya (Jurnal TEDC; Vol 19 No 2 (2025): JURNAL TEDC, 2025)
Based on direct observations made by the author at RSUD Cibabat Cimahi in the file storage room and interviews with medical record officers, problems were found in the medical record file storage room in terms of occupational safety and health, physical factors, namely lighting, noise and work climate, namely lack of lighting and space which felt too dark and damp. The aim of this research is to provide a general description of the physical factors in the medical records storage room and their impact on medical records officers and the controls that have been carried out. The research method used was a qualitative descriptive method and an observational method with a cross sectional approach. The data collection techniques used were observation, interviews and documentation. The subjects in this research were medical records officers in the file storage room at the Cibabat Cimahi Regional General Hospital with the research object being occupational health and safety, the physical factors of lighting, noise and work climate. The results of this research are that the storage space for medical record files in terms of physical factors, lighting and work climate does not comply with Permenkes No. 7 Tahun 2019, namely lighting ranges from 23-81 lux, room temperature ranges from 28-30°C with humidity ranging from 65-68 and the height of the air conditioner is 3 meters above the floor and 0.10 meters so the impact on medical records officers is not yet up to standard Permenkes No. 66 Tahun 2016, while the physical noise factor ranges from 40-49 dBa, which is in accordance with these two standards.